Speaking Out: Housing Issues of Youth in Nunavik - Ikey, Olivia (Études Inuit Studies, 2020)
ContextConference retranscription “Living in Northern Quebec,” special session “Arctic Housing and Community Planning” organized by Mylène Riva and Geneviève Vachon. Arctic Change 2017 Conference, Quebec City, Convention Centre, December 14th, 2017.